ChemInform Abstract: Three‐Component, One‐Pot Sequential Synthesis of Tetracyclic Pyrido[2′, 1′:2, 3]imidazo[5, 1‐a]isoquinolinium Compounds as Potent Anticancer Agents. Issue 11 (8th March 2013) - Zhou, Huayong; Wang, Wei; Khorev, Oleg; Zhang, Yongliang; Miao, Zehong; Meng, Tao; Shen, Jingkang
Abstract Some of the synthesized compounds exhibit relatively strong cytotoxicity against the HeLa cell line.